Penataan Regulasi dalam Upaya Mendukung Restrukturisasi Badan Usaha Milik Negara Perkebunan - Muhammad Iqbal Asnawi; Vita Cita Emia Tarigan; Christian Orchard Perangin-angin; M Permata Sakti; Rommy Yudistira Lubis (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
The formation of a holdingholding to restructure the state-owned plantation industry cannot be separated from the government's ability to control the country's economic engine. Government Regulations Number 72 of 2014 and Number 72 of 2016 which were passed as legalizing the formation of BUMN holdingholding s have sparked controversy and public debate. The fundamental issue of this procedure is the Parent Company's legal obligation to manage the Parent Company. In the relationship between parent companies and subsidiaries, the concept of limited liability presents its own problems. In addition, there is uncertainty regarding legal obligations to third parties. The research methodology is normative law which is supported and obtained from literature data. The findings of this study indicate that the use of the BUMN Law and Limited Liability Company Law as guidelines for managing Plantation BUMNs does not provide the business confidence that Plantation BUMNs need to grow and stay healthy. Considering that the business world continues to develop and the high need for group company management among business actors who carry out business development and expansion, adjustments to these two regulations are very important. The modern business paradigm has resulted in the consolidation of centralized operations in a way that drives growth. As a result, the formation of a holding companyholding company by the government is inappropriate if it is not preceded by changes to the Limited Liability Company Law which provides business certainty for established Plantation BUMNs.